Bacterial survival following shock compression in the GigaPascal range - Hazael, Rachael; Fitzmaurice, Brianna C.; Foglia, Fabrizia; Appleby-Thomas, Gareth J.; McMillan, Paul F. (Elsevier, 2017)
The possibility that life can exist within previously unconsidered habitats is causing us to expand our understanding of potential planetary biospheres. Significant populations of living organisms have been identified at depths extending up to several km below the Earth's surface; whereas laboratory experiments have shown that microbial species can survive following exposure to GigaPascal (GPa) pressures. Understanding the degree to which simple organisms such as microbes survive such extreme pressurization under static compression conditions is being actively investigated. The survival of bacteria under dynamic shock compression is also of interest. Such studies are being partly driven to test the hypothesis of potential transport of biological organisms between planetary systems. Shock compression is also of interest for the potential modification and sterilization of foodstuffs and agricultural products. Here we report the survival of Shewanella oneidensis bacteria exposed to dynamic (shock) compression. The samples examined included: (a) a "wild type" (WT) strain and (b) a "pressure adapted" (PA) population obtained by culturing survivors from static compression experiments to 750 MPa. Following exposure to peak shock pressures of 1.5 and 2.5 GPa the proportion of survivors was established as the number of colony forming units (CFU) present after recovery to ambient conditions. The data were compared with previous results in which the same bacterial samples were exposed to static pressurization to the same pressures, for 15 minutes each. The results indicate that shock compression leads to survival of a significantly greater proportion of both WT and PA organisms. The significantly shorter duration of the pressure pulse during the shock experiments (2-3 μs) likely contributes to the increased survival of the microbial species. One reason for this can involve the crossover from deformable to rigid solid-like mechanical relaxational behavior that occurs for bacterial cell walls on the order of seconds in the time dependent strain rate.